PEMETAAN BIBLIOMETRIK TREN KEBERLANJUTAN PENELITIAN PERILAKU KEUANGAN - Farliana, Nina; Hardianto, Hanif; Ikhsananto, Aan (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This article aims to present a global empirical review of the study of financial behavior related to education, money saving, and consumption, as well as its contribution to research on the Sustainable Development Goals (SDGs) related to social justice in quality education (SDG 4) and gap reduction (SDG 10). Data and metadata from 1180 articles published between 2015 and 2024 were taken from the Scopus database, and analyzed using a bibliometric approach, with the help of classical methodologies and VOSviewer software. The results of the analysis show exponential growth in scientific production over the past few decades, concentration on twelve specific journals indexed in Scopus, the global dominance of United States universities in institutional co-authoring networks, and conceptual separation of financial behavior by theme and time. We conclude that there is a two-decade evolution in relevant topics and concentrates on three main blocks: financial education; savings and consumption decisions; financial and investment literacy, which shows a temporal evolution that results in a variety of visions in the relationship between the development of individual financial behavior and global markets. Given the importance of understanding the impact of education and financial literacy on personal saving, consumption, and investment behavior, further studies of financial behavior can be conducted through this research and assessment of the results obtained